Cybersecurity in Construction: Where Do We Stand and How Do We Get Better Prepared - Mantha, Bharadwaj R. K.; García de Soto, Borja (Frontiers in Built Environment, 2021)
The architecture, engineering, and construction (AEC) industry is increasingly becoming digital and more prone to cyber-attacks. Although there are several studies and standards in the cybersecurity domain, experts suggest that domain-specific studies need to be conducted to address the unique challenges faced within each of the different industries. Therefore, several cybersecurity studies have been conducted for various industries, such as healthcare, manufacturing, telecommunication, and energy. However, this type of study is largely missing in the AEC industry due to different reasons, including lack of awareness. To address that, this study aims to a) compare and analyze the number of cybersecurity-related documents in the AEC industry with several other industries, and b) extract and analyze the cybersecurity-related documents data to identify potential future research trends and topics for the AEC community. The Web of Science (WOS) database, consisting of significant and influential journal publications, was used for document retrieval. VOSviewer was used to identify key research topics and trends in the cybersecurity domain and define future cybersecurity research in the AEC industry. WOS document retrieval results that compared the total number of publications corroborated the little to no attention received to cybersecurity investigation in the AEC industry. In addition, the VOSviewer analysis revealed three significant areas of research in the cybersecurity community that provide a reasonably justified roadmap for conducting cybersecurity research in the AEC industry. This study could greatly benefit the AEC research community and potential reaping benefits to the industry by creating more awareness among different stakeholders.